DEVELOPING SOCIO-EMOTIONAL SKILLS IN EARLY CHILDREN: BEST APPROACHES IN EARLY EDUCATION - Fajriyah, Fajriyah (Jurnal Kajian Pendidikan dan Psikologi, 2023)
This study aims to better understand the optimal way to teach young children social and emotional abilities. A qualitative approach involving a literature review was employed for this investigation. This study used a literature review methodology to investigate the best practices in early childhood education as they pertain to the development of children's social and emotional competencies. The information was gathered through reading and analyzing a wide range of resources on the subject at hand, including books, scholarly journals, articles, and other papers; from these, the researcher identified overarching themes and drew definitive conclusions. This study's findings support the idea that a comprehensive, interdisciplinary approach to early childhood education is optimal for fostering the growth of children's social and emotional competencies. Supportive settings, playtime, role models of appropriate conduct, clear instruction, training for teachers and caregivers, and close cooperation between parents and professionals are all necessary for the development of these abilities. Long-term benefits of fostering children's social and emotional development include positive connections, psychological wellness, and educational success.